Cast of the left bronchial tree. Issue 4 (4th July 2019) - Oudah, Marwa; Sandhu, Hargeet; Sissoho, Fattoumata; Sabath, Bruce
ABSTRACT: A 59-year old woman presented with hemoptysis of thick blood clots and fever of two days duration. Her medical history included sarcoidosis for which she was on chronic steroids. Computed tomography imaging revealed stage IV sarcoidosis with diffuse cystic and fibrotic changes bilaterally, worse in the right lung. She underwent bronchoscopy to attempt to localize a source but none was clearly found; no biopsies were performed. Immediately post-procedure she developed massive hemoptysis with hypoxia leading to cardiopulmonary arrest. She was intubated and stabilized with the spontaneous cessation of her bleeding. Immediate angiography revealed no active extravasation, but localized embolization was performed on the right main and right accessory bronchial arteries because these appeared hypertrophied and irregular. Two days later, she again developed spontaneous massive hemoptysis leading to cardiopulmonary arrest. Manual ventilation through the endotracheal tube became impossible. Immediate bronchoscopy identified a blood clot extending from the main carina into the left main stem bronchus. This was removed with a cryoprobe and ventilation could then be achieved easily. Examination of the blood clot demonstrated it to be a cast of the proximal left bronchial tree. Despite the return of spontaneous circulation via resuscitative efforts, the patient developed acute respiratory distress syndrome and later expired.